Incidence of Tuberculosis in Primary Health Care during the COVID-19 Pandemic: A Longitudinal Study and Perspective from Eastern Indonesia - Firshan Makbul; Darmawati Amir (Masters Program in Public Health, 2024)
Background: Efforts to fight tuberculosis (TB) infection requires a deep understanding of disease control trends to consistently sustain and enhance the identification and treatment of at-risk populations. Indonesia is the third highest globally in TB cases, followed by India and China, accounting for about 10% of all cases. Over the past ten years, Indonesia has witnessed significant TB case reporting and treatment coverage growth. This study aimed to analyze TB case occurrences in a primary health-care setting during the COVID-19 pandemic.Subjects and Method: A cross-sectional study, which included data from the Puskesmas Lau reports from July 2021 to July 2022. A total of 71 patients were conducted using the total sampling method. The collected data were processed descriptively to summarize participants' demographic characteristics and clinical profiles and various important indicators from WHO were analyzed to determine its effectiveness.Results: The center's tuberculosis screening efforts have not reached their optimal level, falling below the national standard of ≥70% for the Case Detection Rate (CDR). However, the treatment success rate (SR) exceeds 90%.Conclusion: The evaluation of the TB control program at Puskesmas Lau reveals achievements in some areas but also highlights challenges posed by the pandemic and the need for strengthened strategies to improve case detection and management. Perceived vulnerability, seriousness, benefit, and barrier, as well as the availability of DOTS treatment, affect treatment adherence. Partnership between patients and health care personnel is recommended to increase the success of TB treatment. Keywords: Tuberculosis, primary health care, COVID-19, longitudinal study, health services